From infancy to early childhood: The role of augmentative manipulation robotic tools in cognitive and social development for children with motor disabilities (2013)
Motor experience plays a critical role in cognitive and social development. Developmental research has identified the major role of motor experience through manipulation and locomotion on the cognitive development of typically developing children. Children with physically disabilities cannot independently explore the environment and manipulate objects, and their motor impairments limit their opportunities for developing cognitive and social skills. Assistive technologies can provide the means for children with disabilities to independently interact with their physical and social environments. Assistive robots can provide children with disabilities with opportunities for object manipulation. This paper describes research using robots to understand and promote cognitive and social development of children with physical disabilities. © 2013, Springer-Verlag Berlin Heidelberg.